Efektivitas Pendekatan Pembelajaran Inklusif dalam Pendidikan Umum: Tinjauan Literatur Terbaru - Ignatius Septo Pramesworo; Muhammad Ni’amul Hanif; Yeyen Herlina (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
The effectiveness of an inclusive learning approach in general education is the extent to which it succeeds in creating a fair and equitable learning environment for all students, regardless of their different abilities, backgrounds or special needs. Inclusive learning seeks to ensure that every student can actively participate and gain maximum benefit from the educational process. It involves adapting the curriculum, teaching methods and assessment to accommodate the different needs of students, including those with disabilities, cultural differences or socio-economic challenges. The effectiveness of this approach is measured through indicators such as increased student access and participation, better academic achievement and positive social-emotional development. Effective inclusive learning approaches not only improve individual student success but also create a more tolerant, supportive and diverse school environment. The review in this study used the literature method. The results show that this approach not only benefits students with special needs, but also positively impacts all students through improved academic and social skills. By using methods such as Universal Design for Learning (UDL), the inclusive approach creates a learning environment that is more responsive to individual differences. In addition, teacher involvement, adequate facilities, and parent and community participation play an important role in the successful implementation of inclusive learning. This study concludes that the integration of inclusive learning in the general education system is an important step towards a more equitable and comprehensive education.